PERAN DISIPLIN KERJA DALAM MEMEDIASI PENGARUH PENGAWASAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II KENDARI - Irwan La Mane; Dedy Takdir Syaifuddin; Nofal Nur; Hasanuddin Bua; Ansir Ansir; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to analyze the effect of supervision, work motivation and work discipline on employee performance. To find out and analyze the effect of supervision and work motivation on work discipline, and see the mediating role of work discipline. This research was conducted at the Institute for Special Child Development Institution Class II Kendari. The population in this study amounted to 46 staff employees, sampling using census techniques with a total sample of 46 people. Research data were collected using a questionnaire and analyzed using Partial Least Square (PLS) analysis. The results of this study indicate that the higher level of supervision conducted will be able to improve work discipline and employee performance. Likewise, the higher work motivation of employees will lead to increased work discipline and employee performance. Work discipline plays a role in mediating the effect of supervision and work motivation on employee performance.This study aims to analyze the effect of supervision, work motivation and work discipline on employee performance. To find out and analyze the effect of supervision and work motivation on work discipline, and see the mediating role of work discipline. This research was conducted at the Institute for Special Child Development Institution Class II Kendari. The population in this study amounted to 46 staff employees, sampling using census techniques with a total sample of 46 people. Research data were collected using a questionnaire and analyzed using Partial Least Square (PLS) analysis.The results of this study indicate that the higher level of supervision conducted will be able to improve work discipline and employee performance. Likewise, the higher work motivation of employees will lead to increased work discipline and employee performance. Work discipline plays a role in mediating the effect of supervision and work motivation on employee performance.